Optimizing seroprotection against pneumococcus in children with nephrotic syndrome using the 13-valent pneumococcal conjugate vaccine. Issue 41 (22nd September 2016) - Pittet, Laure F.; Posfay-Barbe, Klara M.; Chehade, Hassib; Rudin, Christoph; Wilhelm-Bals, Alexandra; Rodriguez, Maria; Siegrist, Claire-Anne; Parvex, Paloma
Abstract: Background: Infections are among the main life-threatening complications in patients with nephrotic syndrome (NS), in particular with Streptococcus pneumoniae, the first cause of bacterial peritonitis and sepsis in these patients. This study aims to evaluate the baseline seroprotection of NS patients against S. pneumoniae, and immunize them with the 13-valent pneumococcal conjugate vaccine (PCV13) regardless of disease activity and previous immunization history, in order to evaluate the immunogenicity, safety profile, and effect of NS treatment on vaccine responses. Methods: This multicentre prospective interventional study enrolled 42 children with NS at disease onset or during a regular follow-up appointment. PCV13 was administered at inclusion. Serotype-specific S. pneumoniae IgG titer were assessed at baseline, after immunization, and at 1 year follow-up. Vaccine safety was evaluated clinically and by urinary tests. Results: PCV13 induced high serotype-specific IgG titers that were maintained at high levels one year after vaccination, even in children previously immunized. No serious adverse event occurred and relapse frequency was unchanged. Conclusion: Given that high IgG titers were achieved and maintained after PCV13 vaccination, and considering the high morbidity related to S. pneumoniae, we propose PCV13 (re-)vaccination for all NS patients, irrespective of their previous immunization history, treatment and disease activity.